Knowledge, attitude, and prevention COVID-19 outbreak of parental children aged 1-6 years - Intarut, Nirun; Thronsao, Maitree (International Journal Of Community Medicine And Public Health, 2022)
Background: Attitude, knowledge and prevention regarding coronavirus disease 2019 (COVID-19) of parents is rarely been found. Therefore, this study aimed to explore attitude, knowledge and prevention regarding COVID-19 of parents of children aged between 1-6 years. Methods: A telephone-based cross-sectional survey was conducted in the northeast of Thailand during August 2021 to September 2021. The survey contained questions on knowledge, attitudes and prevention (KAP) regarding COVID-19. Participants’ demographic characteristics were recorded and analyzed. Multiple linear regression was used to test factors related to attitude, knowledge, and practice towards COVID-19. Results: The result from multiple linear regression analysis showed that females had higher scores of prevention than did males (difference: 3.21; 95% CI: 1.58, 4.83). In addition, parents who were more than 30 years old had lower scores for prevention of COVID-19 (difference: -0.78; 95% CI: -1.46, -0.10). Conclusions: We found associations between parent’s prevention and gender, prevention and age, attitude and occupation, and prevention and occupation towards COVID-19.